2021
DOI: 10.1097/md.0000000000023930
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index monitoring of the clinical effects of propofol closed-loop target-controlled infusion

Abstract: Background: To investigate whether closed-loop systems under bispectral index anesthesia depth monitoring can reduce the intraoperative propofol dosage. Methods: All randomized controlled trials (RCTs) on reducing propofol dosage under closed-loop systems were collected, and the literature was screened out, the abstracts and full texts were carefully read, and the references were tracked, data extraction and quality evaluation were conducted on the included research, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“… 18 Previous studies have shown that propofol is rapidly metabolized in patients and that changes in its plasma concentration or effector compartment concentration are strongly correlated with sedation changes noted through BIS monitoring. 19–21 A prospective trial focusing on the propofol concentration in Chinese patients showed that BIS associated with a 50% probability of loss of consciousness was 58 (58–59). 22 In our study, although remimazolam tosilate injection for induction could reduce BIS, BIS50 was higher using remimazolam tosilate than that using propofol.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Previous studies have shown that propofol is rapidly metabolized in patients and that changes in its plasma concentration or effector compartment concentration are strongly correlated with sedation changes noted through BIS monitoring. 19–21 A prospective trial focusing on the propofol concentration in Chinese patients showed that BIS associated with a 50% probability of loss of consciousness was 58 (58–59). 22 In our study, although remimazolam tosilate injection for induction could reduce BIS, BIS50 was higher using remimazolam tosilate than that using propofol.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the BIS value changes dynamically, it is difficult to maintain BIS at a certain value in conventional anesthesia management methods. The closed-loop target-controlled infusion system used in this study is an anesthesia sedation control system that uses the real-time value of the BIS monitor to feedback and regulate the drug infusion rate, which can ensure that the depth of anesthesia [ 9 ] is accurate to a specific value.There has been a recent study [ 10 ] of the effects of different depth of anesthesia under closed-loop target-controlled infusion on cognitive function and adipocytokine and oxidative stress responses in elderly surgical patients. In this study, the BIS value of the target control pump in the deep anesthesia group was set to 40, and the BIS value of the target control pump in the light anesthesia group was set to 50.…”
Section: Discussionmentioning
confidence: 99%
“…studies suggest that closed loop systems, such as RL, deliver better control of the BIS than does manual control, which may be associated with fewer adverse effects and improved clinical outcomes. 21 Other analyses suggest little difference in clinical effects 22 although they agree that use of closed loop systems reduces variability in the achieved BIS and reduces the total dose of propofol required to maintain anesthesia.…”
Section: How Might This Change Drug Discovery Development And/or Ther...mentioning
confidence: 99%
“…For example, model‐based closed‐loop of propofol administration using BIS as control variable, 15 online Bayesian forecasting of PDs to improve anesthetic drug titration, 16,17 closed‐loop control of administration of vasoactive drugs to control blood pressure, 18 and target controlled infusion for propofol administration 19,20 . Some meta‐analyses of comparative studies suggest that closed loop systems, such as RL, deliver better control of the BIS than does manual control, which may be associated with fewer adverse effects and improved clinical outcomes 21 . Other analyses suggest little difference in clinical effects 22 although they agree that use of closed loop systems reduces variability in the achieved BIS and reduces the total dose of propofol required to maintain anesthesia.…”
Section: Introductionmentioning
confidence: 99%